Tumour-stroma ratio to predict pathological response to neo-adjuvant treatment in rectal cancer. (December 2022) - Strous, M.T.A.; Faes, T.K.E.; Heemskerk, J.; Lohman, B.G.P.M.; Simons, P.C.G.; Janssen Heijnen, M.L.G.; Vogelaar, F.J.; de Bruïne, A.P.
Abstract: Introduction: Management of rectal cancer has advanced, with an increasing use of neoadjuvant chemoradiotherapy (nCRT). This opens options for organ preserving treatment for those with a major response to nCRT. However, the degree of clinical response, based on MRI and post-treatment biopsies, only poorly matches the degree of actual pathological response. In order to select patients with major pathological response without surgical resection, it is of importance to define tumour markers predicting the degree of pathological response to nCRT. The intra-tumoural tumour-stroma ratio (TSR) might be this marker. Methods: TSR in pre-treatment biopsies was estimated according to the method described by van Pelt et al. The degree of pathological response was assessed on the tumour resection according to tumour regression grading (TRG) by Mandard. The primary endpoint of this study was the difference in pathological response to nCRT between TSR-high and TSR-low groups. Results: We found that 26.2% of patients with major response was classified as TSR-high, while 73.8% of patients were classified as TSR-low. A high TSR in pre-treatment biopsies was associated with a lower chance of major-response to nCRT (OR = 0.37, 95%CI; 0.19–0.73), p = 0.004), independent of tumour stage and time between nCRT and surgery. Conclusion: In rectal cancer, TSR in pre-treatment biopsies predicts pathologic response to nCRT, with a high TSR bringing twice the risk of poor to no response compared to low TSR. In future, assessment of TSR may fulfil a role in a therapeutic algorithm identifying patients who will or will not respond to nCRT prior to treatment initiation. Highlights: TSR-assessment is easy and low cost, and the degree of intra- and inter-observer agreement is substantial. 26.2% of patients with major pathological response of rectal cancer to nCRT is classified as TSR-high in pre-treatment biopsies. High-TSR in pre-treatment biopsies of rectal cancer is associated with a lower chance of major pathological response to nCRT (OR = 0.37, 95%CI; 0.19–0.73), p = 0.004), independent of tumour stage and time between nCRT and surgery.